2016
DOI: 10.1051/matecconf/20164704013
|View full text |Cite
|
Sign up to set email alerts
|

The Insight of Industrialised Building System (IBS) By Bumiputera Construction Players

Abstract: Abstract. The term Industrialised Building System (IBS) is widely recognised by construction players in Malaysia since its first implementation since 1960s for IBS pilot projects of Pekeliling Flats and Rifle Range Flats. The aim for the implementation is to promote better system in delivering construction end-products which offers efficiency and effectiveness. At the same time, Bumiputera construction players are the majority of parties in construction industry especially in Small and Medium Enterprises (SMEs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Another aspect of the application includes the maintenance management system (Z.-A. Ismail et al, 2018) and the involvement of Bumiputera construction players in IBS (Muhammad et al, 2016). Further, Nawi et al (2018) suggested supply chain management as part of the application strategy and proposed WhatsApp as an effective communication platform in IBS management on site (Pozin & Nawi, 2018).…”
Section: Applicationmentioning
confidence: 99%
“…Another aspect of the application includes the maintenance management system (Z.-A. Ismail et al, 2018) and the involvement of Bumiputera construction players in IBS (Muhammad et al, 2016). Further, Nawi et al (2018) suggested supply chain management as part of the application strategy and proposed WhatsApp as an effective communication platform in IBS management on site (Pozin & Nawi, 2018).…”
Section: Applicationmentioning
confidence: 99%
“…The loading capacity of hoists and cranes for installation of precast concrete components need to be considered based on their weight and size [32,30]. High accuracy and efficiency when handling IBS components are essential by properly coordinate them during installation and storage [33] with the purpose to avoid a serious problems such as delay and wastage.…”
Section: Installation and Constructionmentioning
confidence: 99%